OPTIMALIZATION OF LEGAL PROTECTION FOR FEMALE HOUSEMAIDS IN INDONESIA - Marzellina Hardiyanti; Ani Purwanti (Diponegoro Law Review, 2019)
Housemaids are one of the most vulnerable groups to violence and unfair wage. The problem is that, in Indonesia, female comprised 90% of the housemaids, thus making them even more vulnerable. Several cases of physical, psychological, and sexual violence that happened against housemaids are due to discriminative environment. This problem is what urges for the access of justice for female housemaids in Indonesia, thus the focus of this article. The research of this article used the normative legal approach based on literature studies and descriptive analysis towards the problem. The urgency of legal protection for female housemaids in Indonesia is caused by the prevalence of domestic violence and unfair compensation. Therefore, a comprehensive and exhaustive legal framework is needed to provide a sufficient access of justice mechanism for female housemaids, such as a legislative act specified for them. Rehabilitation is also a vital mechanism, especially to housemaids who suffered from violence by providing them temporary shelters, counseling, and protection from retalitation.